HIV‐1 gp41 transmembrane oligomerization monitored by FRET and FCS. Issue 6 (5th March 2018) - Schroeder, Sabrina; Kaufman, Joshua D.; Grunwald, Matthias; Walla, Peter J.; Lakomek, Nils‐Alexander; Wingfield, Paul T.
Abstract : The HIV‐1 envelope gp120/gp41 trimer mediates viral membrane fusion. After cluster of differentiation‐4 recognition, gp120 detaches from the virus, exposing gp41 which triggers fusion. During the fusion process, gp41 may not remain trimeric, which could have functional importance. Here, we probe the reversible association of full length gp41 (minus the cytoplasmic domain) in detergent micelles (with probes attached to transmembrane domain) by fluorescence resonance energy transfer (FRET) with a μm dissociation constant. This is compared with other methods. A gp41‐targeted fusion inhibitor must interfere with this transition, and monomeric, partially monomeric or trimeric states all present potential binding epitopes. The gp41 self‐association is a valid drug target model and FRET, a potential high‐throughput assay system, could be used to screen drug libraries. Abstract :